PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI KELAS II-B PADA MATERI PATUH ATURAN DI SDIT AL USWAH SURABAYA - Uly Ajnihatin; Yuni Gayatri; Ni Luh Putu Sari Murthi (Universitas Muhammadiyah Surabaya, 2024)
This study aims to improve the learning outcomes of class II-B students at SDIT Al Uswah Surabaya through the application of the Problem Based Learning model on the material of Obeying The Rules. The type of research used is pseudo-experimental research. The research design was posttest only group design. The subjects of the research conducted were class II-B students of Sdit Al Uswah Surabaya, totaling 28 people in the 2023/2024 school year. Data collection techniques by means of observation and tests. The research instrument used a learning implementation observation sheet and cognitive test sheet. The results of this study indicate that all stages of project-based learning are well implemented. The results of observations of students' attitudes show 96,4% meet KKTP, the results of students' skill 100% meet KKTP and the learning outcomes of students show 89% meet KKTP. The results of the reflection showed that all students felt happy and could understand the material taught. The conclusion of this study is that the application of the problem based learning model effectively improves student outcomes.